EVALUATION OF ANTIDEPRESSANT ACTIVITY OF TOPIRAMATE IN MICE - Aithal, Sathisha; V Hooli, Tanuja; Patil, Rajini; H V, Varun; E S, Swetha (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Â Objective: To study the antidepressant activity of topiramate in experimental models Â Methods: Topiramate (15mg/kg), amitriptyline (10mg/kg) and combination of both topiramate (7.5mg/kg) and amitriptyline (5mg/kg) were administered to different groups of albino mice daily for fourteen days. The immobility period was recorded on day one and day fourteen in both forced swim test and tail suspension test. The P value less than 0.05 was considered as statistically significant Â Results: There was a statistically significant reduction in the immobility period in animals treated with topiramate compared to control group in both experiments on day one and day fourteen (P<0.05). There was also statistically significant difference in immobility period in the group treated with both topiramate and amitriptyline compared to group of animals treated with topiramate alone. There was no statistically significant difference in the immobility period between groups of animals treated with topiramate (15mg/kg) and amitriptyline (10mg/kg) alone. Â Conclusion: Topiramate at a dose of 15 mg/kg has demonstrated antidepressant activity which was comparable to amitriptyline. There was synergism in antidepressant activity of topiramate and amitriptyline. Â Key words: Depression, Forced swim test, Tail suspension test